Thermoelectric material, its manufacturing method and thermoelectric generation element
By orienting chromium silicide particles in the c-axis direction within a sintered body and using a magnetic field during solidification, the thermoelectric properties of chromium silicide polycrystals are significantly improved, achieving performance comparable to single crystals while simplifying the manufacturing process.
Patent Information
- Application Number
- JP2021103696
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-23
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2041-06-23
AI Technical Summary
Chromium silicide polycrystals suffer from inferior thermoelectric properties due to high thermal conductivity caused by phonon scattering at grain boundaries, which limits the utilization of superior c-axis orientation properties and results in a small Seebeck coefficient.
A sintered body of chromium silicide with particles oriented in the c-axis direction is created using a manufacturing method involving the dispersion of chromium silicide powder in a solvent, solidification under a magnetic field, and subsequent sintering, which enhances the power factor and thermoelectric properties comparable to single crystals.
The c-axis oriented sintered chromium silicide exhibits thermoelectric properties equivalent to those of single crystals, including a high power factor, reduced thermal conductivity, and increased Seebeck coefficient, while simplifying the manufacturing process and reducing costs.
Smart Images

Figure 0007656911000006 
Figure 0007656911000007 
Figure 0007656911000008
Abstract
Description
[Technical Field]
[0001] The present invention relates to a thermoelectric material, a method for producing the same, and a thermoelectric power generating element using the same. [Background technology]
[0002] Even in Japan, where energy conservation has progressed particularly well compared to other countries in the world, approximately three-quarters of the primary energy supply is currently discarded as thermal energy in waste heat recovery. Under these circumstances, thermoelectric conversion elements are attracting attention as solid-state elements that can recover thermal energy and convert it directly into electrical energy.
[0003] In addition to excellent thermoelectric properties, thermoelectric materials used in such thermoelectric conversion elements are required to be low-cost, made from harmless elements, and to have mechanical properties and chemical stability. Among such thermoelectric materials, active research has been conducted on transition metal silicides, such as chromium silicide (CrSi2). According to Non-Patent Document 1, hexagonal chromium silicide single crystals are known to have a higher power factor along the c-axis than along the a-axis. However, in chromium silicide polycrystals, the advantageous properties of the c-axis orientation cannot be utilized. Because of high thermal conductivity due to phonon scattering at grain boundaries, the Seebeck coefficient is low, and improvements are needed. [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] F.Yu.Solomkin et al.,Technical Physics,2013,Vol.58,No.2,pp.289-293 Summary of the Invention [Problem to be solved by the invention]
[0005] In view of the above, an object of the present invention is to provide a thermoelectric material made of polycrystal containing chromium silicide and having excellent thermoelectric properties, a method for producing the same, and a thermoelectric power generating element. [Means for solving the problem]
[0006] The thermoelectric material according to the present invention is made of a sintered body made of grains containing chromium silicide (CrSi2) as a main component, and the grains are oriented in the c-axis direction, thereby solving the above-mentioned problems. f in the thickness direction of the sintered body L The value (Lotgering Factor in the 0003 direction) may range from 0.5 to 1, inclusive. said f L The value (Lotgering Factor in the 0003 direction) may range from 0.53 to 0.95. The particle size may be in the range of 0.5 μm to 1.5 μm. The density of the sintered body may be 95% or more. A portion of the silicon in the chromium silicide may be substituted with an element selected from the group consisting of germanium (Ge), vanadium (V), aluminum (Al), zirconium (Zr), niobium (Nb), and copper (Cu). A portion of the chromium in the chromium silicide may be substituted with an element selected from the group consisting of manganese (Mn) and rhenium (Re). The particles may further contain a second phase which is a chromium silicide. The second phase may have a cubic crystal structure and belong to the P213 space group. The second phase may be contained in an amount of more than 0 mass % to 6 mass %. The method for manufacturing the thermoelectric material according to the present invention includes dispersing a raw material powder mainly composed of chromium silicide (CrSi2) in a solvent to prepare a raw material slurry, solidifying and molding the raw material slurry while applying a magnetic field to form a molded body, and sintering the molded body, thereby solving the above-mentioned problem. The solvent may be an aliphatic hydrocarbon selected from the group consisting of pentane, hexane, heptane and octane, or an alcohol selected from the group consisting of methanol, ethanol and propanol. The particle size (median diameter D50) of the raw material powder may be in the range of 350 nm or more and 550 nm or less. The magnetic field may be in the range of 8T to 14T. The forming of the compact may be performed by slip casting. The density of the compact may be in the range of 40% or more and 70% or less. The sintering may be performed at a temperature in the range of 1373K or more and 1773K or less. The method may further include pressing the green body prior to or simultaneously with the sintering. The thermoelectric power generation element according to the present invention includes p-type thermoelectric materials and n-type thermoelectric materials alternately connected in series, and the p-type thermoelectric materials and / or the n-type thermoelectric materials are the above-mentioned thermoelectric materials, thereby solving the above-mentioned problems. [Effects of the Invention]
[0007] The thermoelectric material of the present invention is a sintered body made of particles whose main component is chromium silicide (CrSi2), and is characterized in that the particles are oriented in the c-axis direction. Because of the c-axis orientation, it can achieve a power factor equivalent to that of a single crystal of chromium silicide. Thermoelectric materials made of such sintered bodies are used in thermoelectric conversion elements.
[0008] The method for manufacturing a thermoelectric material of the present invention involves dispersing a raw material powder primarily composed of chromium silicide (CrSi2) in a solvent to prepare a raw material slurry, molding the raw material slurry while applying a magnetic field to form a compact, and sintering the compact. By applying a magnetic field, the particles are oriented in the c-axis direction, parallel to the magnetic field application direction. This method eliminates the need for single crystal growth techniques and advantageously reduces manufacturing costs, as a sintered body with thermoelectric properties equivalent to those of a single crystal can be obtained simply by applying a magnetic field. [Brief explanation of the drawings]
[0009] [Figure 1] Schematic diagram showing the thermoelectric material of the present invention. [Figure 2] Flowchart showing the manufacturing process of the thermoelectric material of the present invention [Figure 3] Schematic diagram showing a thermoelectric conversion element of the present invention. [Figure 4] Diagram showing a micrograph of an ingot [Figure 5] XRD pattern of the prepared raw material powder [Figure 6] SEM image of raw powder [Figure 7] Diagram showing particle size distribution of raw material powder [Figure 8] Procedure showing part of the manufacturing process of the sintered body of Examples 1 and 2 [Figure 9] 1 shows XRD patterns of sintered bodies of Examples 1 to 4. [Figure 10] 1 shows an SEM image and an EDX image of the sintered body of Example 1. [Figure 11] A diagram showing the crystal orientations from electron backscatter diffraction (EBSD) on the ND plane of the sintered bodies of Examples 1, 3, and 4. [Figure 12] FIG. 10 is a graph showing the temperature dependence of the electrical resistivity of the sintered bodies of Examples 1 to 4. [Figure 13] FIG. 1 shows the temperature dependence of the Seebeck coefficient of the sintered bodies of Examples 1 to 4. [Figure 14] FIG. 10 is a graph showing the temperature dependence of the power factor of the sintered bodies of Examples 1 to 4. [Figure 15] FIG. 10 is a graph showing the temperature dependence of the thermal conductivity of the sintered bodies of Examples 1 to 4. [Figure 16] FIG. 10 is a graph showing the temperature dependence of the dimensionless figure of merit ZT of the sintered bodies of Examples 1 to 4. [Figure 17] Graph showing the relationship between the dimensionless figure of merit ZT and the fL value of the sintered bodies of Examples 1 to 4. DETAILED DESCRIPTION OF THE INVENTION
[0010] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Note that like elements are designated by like numbers and their description will be omitted.
[0011] (Embodiment 1) In the first embodiment, a thermoelectric material and a method for producing the same according to the present invention will be described. FIG. 1 is a schematic diagram showing a thermoelectric material of the present invention.
[0012] The thermoelectric material of the present invention comprises a sintered body 100 made of particles 110 whose main component is chromium silicide (CrSi2). Chromium silicide is known as a thermoelectric material made of a low-cost, harmless element. Furthermore, in the thermoelectric material of the present invention, the particles 110 are oriented in the c-axis direction, as shown in FIG. 1. As such, even though it is a sintered body 100, because the particles 110 are c-axis oriented, it is possible to achieve a power factor equivalent to that of a bulk single crystal of chromium silicide. This will be explained in detail below.
[0013] Here, the chromium silicide crystal belongs to the hexagonal crystal system, the P6222 space group (the 180th space group of the International Tables for Crystallography), and has the crystal structure parameters (atomic coordinate positions) shown in Table 1.
[0014] [Table 1]
[0015] The particles 110 may be a single crystal of a single chromium silicide phase, or a single crystal with a chromium silicide matrix to which a dopant has been added. Although the lattice constant changes when the Cr and Si composition is slightly off the stoichiometric ratio due to defects or when part of the chromium (Cr) or silicon (Si) is replaced with another element, the crystal structure and the atomic positions determined by the sites and their coordinates do not change significantly enough to break the chemical bonds between the skeletal atoms. Therefore, if the length of the Cr-Si chemical bond (nearest neighbor distance) calculated from the lattice constant and atomic coordinates obtained by La Bail analysis of the results of X-ray diffraction or neutron diffraction for the P6222 space group of the target sintered body is within ±5% of the length calculated from the lattice constant and atomic coordinates of the crystal shown in Table 1, the sintered body 100 may be determined to be composed of particles 110 primarily composed of chromium silicide.
[0016] When the deviation in composition or the amount of addition (substitution amount) is small, it can be easily determined that the crystal structure is the same as that of CrSi2 when the lattice constant calculated from the X-ray diffraction results measured for the sintered body in question and the diffraction peak positions (2θ) calculated using the crystal structure data in Table 1 match for the main peaks (e.g., eight peaks).
[0017] When the particles 110 are made of undoped chromium silicide single crystal, they become p-type semiconductors and function as p-type thermoelectric materials. However, to adjust the carrier concentration, some of the Si in the chromium silicide may be substituted with an element selected from the group consisting of germanium (Ge), vanadium (V), aluminum (Al), zirconium (Zr), niobium (Nb), and copper (Cu). This increases the Seebeck coefficient. Among these, Ge is preferred. The amount of addition is adjusted as appropriate within a range that does not change the crystal structure, but may be, for example, in the range of 0.5 at% to 5 at%. Within this range, the carrier concentration can be easily adjusted.
[0018] Alternatively, a portion of the Cr in the chromium silicide may be substituted with an element selected from the group consisting of manganese (Mn) and rhenium (Re). This makes the particles 110 an n-type semiconductor and functions as an n-type thermoelectric material. Among these, Mn is preferred. The amount of addition is adjusted appropriately within a range that does not change the crystal structure, but may be, for example, in the range of 15 at % to 25 at %. Within this range, the particles become an n-type semiconductor, and a high Seebeck coefficient is likely to be obtained.
[0019] The particles 110 preferably consist of a single phase of doped / undoped chromium silicide, but may contain a second phase to the extent that the thermoelectric properties are not impaired. Examples of such a second phase include chromium silicide containing Cr and Si, and preferably CrSi, which has a cubic crystal structure and belongs to the space group P213. CrSi is preferred because it does not impair the thermoelectric properties of chromium silicide. Since chromium silicide is permitted as a second phase generated during manufacturing, manufacturing conditions are relaxed, which is advantageous for improving yield.
[0020] The content of the second phase contained in the particles 110 is preferably more than 0 mass% and not more than 15 mass%. Within this range, the thermoelectric properties are not impaired. The content of the second phase is more preferably more than 0 mass% and not more than 10 mass%, even more preferably more than 0 mass% and not more than 6 mass%, and even more preferably 1 mass% to 5 mass%. In this specification, the content is calculated by Rietveld analysis of an X-ray diffraction pattern. From this perspective, in this specification, the amount of chromium silicide as a main component in the sintered body 100 is more than 85 mass%, preferably 90 mass% or more, and more preferably more than 94 mass%.
[0021] The particle size of the particles 110 is not particularly limited, but is preferably in the range of 0.5 μm to 1.5 μm. Within this range, the particles 100 can be efficiently c-axis oriented. More preferably, the particle size of the particles 110 is in the range of more than 0.85 μm to 1.0 μm. Even more preferably, the particle size of the particles 110 is in the range of 0.88 μm to 0.92 μm. In this specification, the particle size is calculated as the equivalent circular diameter from the area of the crystal grain by electron backscatter diffraction (EBSD) using an electron microscope such as a scanning electron microscope. The area of the crystal grain is calculated from the step width during measurement and the number of data points within the crystal grain.
[0022] The sintered body 100 of the present invention is characterized in that the grains 110 are c-axis oriented. In this specification, c-axis orientation means that the peak intensity of the peak corresponding to the (0003) plane is the highest in the X-ray diffraction pattern obtained when X-ray diffraction measurement is performed on a polished sintered body.
[0023] In the sintered body 100 of the present invention, preferably, f LThe value of f (Lotgering Factor in the 0003 direction) is in the range of 0.5 to 1. When the particles 110 are c-axially oriented so as to satisfy this range, a large power factor is obtained, and excellent thermoelectric properties are obtained. More preferably, L The value is in the range of 0.53 to 0.95, inclusive. Within this range, a large power factor and particularly excellent thermoelectric properties can be obtained.
[0024] f L The value is calculated by the following formula: f L =(P-P0) / (1-P0) P0=(ΣI0(000m)) / (ΣI0(hklm)) P=(ΣI(000m)) / (ΣI(hklm)) Here, ΣI0(000m) is the sum of the measured peak intensities of the (0003) and (0006) diffraction planes among all diffraction planes in the XRD measurement range of the sintered body of interest, where 2θ is in the range of 20 to 100°, and ΣI0(hklm) is the sum of the measured peak intensities of all diffraction planes of the sintered body of interest. ΣI(000m) is the calculated value of the peak intensities of the (0003) and (0006) diffraction planes among all diffraction planes of the standard sample, and ΣI0(hklm) is the sum of the calculated value of the peak intensities of all diffraction planes of the standard sample. The standard sample may be a powder sample or an ICDD card. For example, in the case of a polycrystalline powder, f L = 0 (P = P0), and if it is a single crystal, f L = 1 (P = 1), but even in polycrystals, if the deviation of the c-axis of all crystal grains is small (for example, within 10 degrees), f L However, f L Even if a polycrystal satisfies ρ=1, the XRD pattern measured from a different direction will differ from that of a single crystal, making it easy to distinguish between polycrystals and single crystals.
[0025] In this way, the present inventors have found that even if a bulk single crystal of chromium silicide (CrSi) is not used, a sintered body of chromium silicide with a c-axis orientation within the above-mentioned range can provide excellent thermoelectric properties comparable to those of a bulk single crystal. This makes it possible to eliminate the need for advanced techniques and expensive equipment required for growing bulk single crystals, making the thermoelectric material made of the sintered body 100 of the present invention extremely effective.
[0026] Although there is no particular limitation on the sintered density of the sintered body 100 of the present invention, it is preferably 95% or higher. This reduces voids and holes between the particles 110, resulting in high thermoelectric properties. The sintered density is more preferably 96% or higher, and even more preferably 98% or higher. Note that the sintered density in this specification is measured by Archimedes' method and is expressed as a percentage (relative density) of the true density.
[0027] Next, a method for producing a thermoelectric material made of the sintered body 100 of the present invention will be described. FIG. 2 is a flowchart showing the manufacturing process of the thermoelectric material of the present invention.
[0028] The thermoelectric material made of the sintered body 100 of the present invention is obtained by the following steps S210 to S230. Step S210: A raw material powder containing chromium silicide (CrSi2) as a main component is dispersed in a solvent to prepare a raw material slurry. Step S220: The raw material slurry is solidified and molded while a magnetic field is applied to form a molded body. Step S230: The compact is sintered. In step S220, a magnetic field is applied, so that the raw material powder consisting of single crystal particles is oriented so that their c-axes are parallel to the direction of the applied magnetic field. The compact thus obtained is sintered in step S230, thereby obtaining the sintered body 100 described above. Each step will be described in detail below.
[0029] In step S210, the raw material powder mainly composed of chromium silicide has each particle composed of a single crystal, and is the chromium silicide described with reference to Fig. 1. The raw material powder may also be chromium silicide in which part of Si is substituted with other elements such as Ge, or part of Cr is substituted with other elements such as Mn. The amount of addition (substitution amount) is as described above.
[0030] In step S210, the content of the raw material powder in the raw material slurry is preferably in the range of 10 mass% to 30 mass%. Within this range, the raw material powder can be dispersed well. The content of the raw material powder is more preferably in the range of 15 mass% to 25 mass%.
[0031] The particle size (median diameter D50) of the raw material powder is preferably in the range of 350 nm to 550 nm. Within this range, the raw material powder can be well dispersed in a solvent and is likely to be c-axis oriented in step S220, which will be described later. The particle size (median diameter D50) of the raw material powder is more preferably in the range of 380 nm to 425 nm.
[0032] In step S210, the solvent is not particularly limited as long as it disperses the raw material powder, but a solvent with low viscosity and no reactivity with chromium silicide is selected. The solvent is preferably an aliphatic hydrocarbon selected from the group consisting of pentane, hexane, heptane, and octane, or an alcohol selected from the group consisting of methanol, ethanol, and propanol. These solvents can promote the dispersion of the raw material powder. Among them, alcohols such as ethanol are preferred.
[0033] In step S210, a polycationic polymer or a polyanionic polymer may be further added. This coats the particles of the raw material powder with the polymer, and the particles are dispersed well due to electrostatic repulsion. As a result, in step S220, the rotation of the particles is promoted by applying a magnetic field, and f L A c-axis oriented sintered body having a value of 0.5 or more can be obtained.
[0034] Examples of polycationic polymers include trialkylamines (PAM), polyethyleneimines (PEI), polylysines (PL), polypeptides, chitosan, polysaccharides, and copolymers thereof. Examples of polyanionic polymers include ammonium polycarboxylate, polystyrene sulfonate, polyacrylate, polymethacrylate, polyvinyl sulfate, polyphosphate, carrageenan, gellan gum, carboxymethyl cellulose, carboxymethyl agarose, carboxymethyl dextran, carboxymethyl chitin, carboxymethyl chitosan, polymers modified with carboxymethyl groups, and alginate.
[0035] The amount of polycationic polymer or polyanionic polymer added may be, for example, in the range of more than 0 mass% to not more than 5 mass%, preferably in the range of more than 0 mass% to not more than 1 mass%, and more preferably in the range of more than 0 mass% to not more than 0.5 mass%. L A sintered body having a value in the range of 0.53 to 0.95 can be obtained.
[0036] In step S210, an acid or alkali may be added to the raw slurry, which will further disperse the particles.
[0037] In step S220, the raw material slurry is solidified and molded in a magnetic field to obtain a molded body. The magnetic field applied is preferably in the range of 8 T (tesla) or more and 14 T or less. This range can promote particle rotation. The magnetic field applied is more preferably in the range of 10 T or more and 14 T or less. This range causes the particles to rotate, further promoting c-axis orientation.
[0038] In step S220, the direction of application of the magnetic field can be selected arbitrarily, such as a direction parallel to gravity or a direction perpendicular to gravity, etc. This allows for an orientation direction that corresponds to the method of applying the magnetic field, without being limited by the molding direction or shape.
[0039] In step S220, various methods may be appropriately employed for solidification. Solidification methods include slip casting, pressure filtration, tape casting, and electrophoretic deposition. Among these, slip casting is preferred because it can produce a green body with good c-axis orientation and has no shape limitations. By employing slip casting, a magnetic field can be applied in any direction, even for complex shapes, making it possible to obtain a sintered body with c-axis orientation in any direction.
[0040] In step S220, the density of the compact is preferably in the range of 40% to 70%. This allows a sintered body having a sintered density of 96% or more to be obtained by sintering in the subsequent step S230. The density of the compact is measured by the Archimedes method.
[0041] Following step S220, the compact may be pressed using, for example, a cold isostatic press (CIP) device, which can result in a high-density sintered compact through subsequent sintering in step S230.
[0042] In step S230, the sintering of the compact is preferably carried out in a temperature range of 1373 K or more and 1773 K or less. Within this range, grain growth occurs, resulting in a sintered body with a high density. Sintering is more preferably carried out in a temperature range of 1423 K or more and 1623 K or less. Within this range, grain growth is promoted, resulting in a sintered body with a higher density.
[0043] In step S230, the sintering method is not particularly limited, and spark plasma sintering (SPS), atmospheric sintering, hot press (HP) sintering, and hot isostatic pressing (HIP) sintering can be appropriately used. The sintering time varies depending on the sintering method, but for example, when spark plasma sintering (SPS) is used, it may be 5 minutes or more and 30 minutes or less.
[0044] In step S230, the compact may be sintered under pressure so that HP sintering or HIP sintering can be employed, thereby obtaining a sintered body with a higher density. In this manner, a thermoelectric material made of the sintered body 100 of the present invention is obtained.
[0045] (Embodiment 2) In the second embodiment, a thermoelectric conversion element using the thermoelectric material of the present invention will be described. FIG. 3 is a schematic diagram showing a thermoelectric conversion element of the present invention.
[0046] A thermoelectric power generating element 300 according to the present invention includes a pair of n-type and p-type thermoelectric materials 310 and 320, and electrodes 330 and 340 at the ends of each of these materials. The electrodes 330 and 340 electrically connect the n-type and p-type thermoelectric materials 310 and 320 in series.
[0047] Here, the p-type thermoelectric material 310 and / or the n-type thermoelectric material 320 is the thermoelectric material 100 of the present invention described in embodiment 1. When using the thermoelectric material of the present invention for both the p-type and the n-type, it is sufficient to use materials with different carrier types, or materials with the same carrier type but different Seebeck coefficients.
[0048] Alternatively, when the thermoelectric material of the present invention is used as the p-type thermoelectric material 310, an n-type thermoelectric material such as an MgSi-based, ZnSb-based, or ZnO-based material that has high thermoelectric performance at temperatures from 300 K to 773 K can be used. An exemplary composition of an MgSi-based material is, for example, Mg2Si 0.4 Sn 0.6 , Mg2Si 0.37 Sn 0.6 B 0.03 An exemplary composition of SiGe is, for example, Si 0.8 Ge 0.2 An exemplary composition of ZnO is, for example, Zn 0.98 Al 0.02 It is O.
[0049] Alternatively, when the thermoelectric material of the present invention is used as the n-type thermoelectric material 320, p-type thermoelectric materials such as BiSbTe, MgAgSb, and AgSbSe, which have high thermoelectric performance at temperatures from 300 K to 773 K, can be used. Exemplary compositions of BiSbTe include, for example, Bi0.5 Sb 1.5 Te3, Bi 0.4 Sb 1.6 Te3. Exemplary compositions of the MgAgSb system include, for example, MgAgSb, MgAg 0.965 Ni 0.005 Sb 0.99 An exemplary composition of the AgSbSe system is, for example, AgSbSe2. Note that these are examples and are not limiting.
[0050] The electrodes 330, 340 can be made of a common electrode material, such as Fe, Ag, Al, Ni, or Cu. The electrodes 330, 340 are arranged perpendicular to the c-axis direction of the thermoelectric material of the present invention. This allows the sintered body to exhibit excellent thermoelectric performance comparable to that of a bulk single crystal chromium silicide.
[0051] 3 shows a state in which a chip made of n-type thermoelectric material 310 is joined by solder or the like to an electrode 340 on the low-temperature side, and an opposite end of the chip of n-type thermoelectric material 310 is joined by solder or the like to an electrode 330 on the high-temperature side. Similarly, a chip made of p-type thermoelectric material 320 is joined by solder or the like to an electrode 330 on the high-temperature side, and an opposite end of the chip of p-type thermoelectric material 320 is joined by solder or the like to an electrode 340 on the low-temperature side.
[0052] When the thermoelectric power generation element 300 of the present invention is placed in an environment where the electrode 330 is at a high temperature and the electrode 340 is at a lower temperature than the electrode 330, and the end electrodes are connected to an electric circuit or the like, a voltage is generated due to the Seebeck effect, and a current flows in the order of the electrode 340, the n-type thermoelectric material 310, the electrode 330, and the p-type thermoelectric material 320, as shown by the arrows in Figure 3. In detail, the electrons in the n-type thermoelectric material 310 obtain thermal energy from the electrode 330 on the high-temperature side, move to the electrode 340 on the low-temperature side, and release the thermal energy there, and in response, the holes in the p-type thermoelectric material 320 obtain thermal energy from the electrode 330 on the high-temperature side, move to the electrode 340 on the low-temperature side, and release the thermal energy there.
[0053] 3, a π-type thermoelectric power generation element is used for the explanation, but the thermoelectric material of the present invention may also be used in a U-type thermoelectric power generation element (not shown). In this case as well, n-type thermoelectric materials and p-type thermoelectric materials made of the thermoelectric material of the present invention are alternately connected electrically in series.
[0054] The present invention will now be described in detail using specific examples, but it should be noted that the present invention is not limited to these examples. [Example]
[0055] [Preparation of chromium silicide powder] Chromium silicide (CrSi2) powder was synthesized by arc melting a mixture of chromium chips (Sigma-Aldrich, purity 99.995%) and silicon pieces (Sigma-Aldrich, purity 99.95%) in a stoichiometric ratio. The resulting ingot was remelted repeatedly to homogenize it. The weight loss was less than 0.2 mass%. The ingot was observed with a tabletop microscope (Hitachi High-Technologies Corporation, TM3000). The results are shown in Figure 4.
[0056] The ingot was crushed and powdered using a wet ball mill using a planetary ball mill (Fritsch, Pulverisette 7). The coarsely crushed ingot and crushing balls (yttria-stabilized zirconia, φ=5 mm) were placed in a crushing container (made of yttria-stabilized zirconia) so that the mass ratio of crushing balls to powder was 5. An aqueous ethanol solution (15% by volume) was then added, and the mixture was milled at a rotation speed of 200 rpm for 8 hours. The resulting powder was dried at 373 K overnight.
[0057] The obtained powder was identified by X-ray diffraction. For X-ray diffraction, a rotating Cu-X-ray tube (λ Kα1 =1.5406Å, λ Kα2 =1.5444Å, λ Kα2 / λ Kα1A θ-2θ Rigaku TTRAXIII diffractometer (Rigaku Corporation) equipped with a θ = 0.5 and a DTex detector was used. The incident beam size was set to approximately 500 μm in diameter, and diffraction patterns were measured over the 2θ range of 5° to 130° with a step width of 0.02°. XRD patterns were analyzed using MAUD (Materials Analysis Using Diffraction, an open-source, public domain software). The results are shown in Figure 5.
[0058] The morphology of the obtained powder was observed using a field emission scanning electron microscope (JEOL Ltd., JSM-7000F). The observation results are shown in Figure 6. The particle size distribution of the obtained powder was determined by dynamic light scattering (DLS) using a Microtrac Nanotrac ULTRA device. The results are shown in Figure 7.
[0059] The above results are summarized below. FIG. 4 shows a micrograph of the ingot.
[0060] According to Figure 4, the ingot consisted mostly of macro-sized crystals exceeding 100 μm.
[0061] FIG. 5 shows the XRD pattern of the prepared raw material powder.
[0062] According to Figure 5, all diffraction peaks were indexed to the CrSi2 crystal (space group P6222, number 180) shown in Table 1, and La Bail analysis revealed that the lattice constants a (= b) and c were a = 4.42724(6) Å and c = 6.36194(9) Å, respectively. This confirmed that the raw material powder obtained was CrSi2.
[0063] FIG. 6 is a diagram showing an SEM image of the raw material powder. FIG. 7 is a diagram showing the particle size distribution of the raw material powder.
[0064] As shown in Figure 6, the raw material powder was successfully pulverized by the ball mill. As shown in Figure 7, the particle size distribution showed an average particle size (D50) of 405 nm and a standard deviation of 132 nm. The pulverized powder consisted of CrSi2 single crystal particles.
[0065] [Example 1 to Example 3] In Examples 1 to 3, the prepared chromium silicide powder was used to produce a sintered body by slip-casting a molded body and sintering it while applying a magnetic field. FIG. 8 is a procedure showing part of the manufacturing process of the sintered bodies of Examples 1 and 2.
[0066] The prepared chromium silicide powder 810 was dispersed in absolute ethanol 820, and the solid phase concentration was adjusted according to Table 2 (step S210 in FIG. 2). Furthermore, according to Table 2, polyethyleneimine (PEI, manufactured by Sigma-Aldrich, average molar mass (g / mol) = 10,000, linear) was added as a polycationic polymer to the raw material slurry, and the acidity was adjusted with 0.1 vol% of acetic acid. The raw material slurry was ultrasonically treated to disperse aggregates.
[0067] Next, the raw material slurry was solidified and molded while applying a magnetic field to form a green body (step S220 in Figure 2). The raw material slurry was poured into a slip-cast setup consisting of a cylindrical polyethylene mold 850 (φ = 12 mm, height = 40 mm) placed on a porous alumina plate 840 covered with a membrane filter 830 (porosity 200 nm). To prevent evaporation of ethanol, the polyethylene mold 850 was covered with a plastic film 860.
[0068] The slip-cast setup was placed in a 12 T superconducting magnet, and a 12 T magnetic field was applied parallel to the direction of gravity (arrow B in FIG. 8). At this time, ethanol slowly flowed out through the pores of the membrane filter 830 and the porous alumina plate 840 (arrow SC in FIG. 8). In this way, a compact 870 was obtained. The compact 870 was then pressed at 394 MPa for 10 minutes using a cold isostatic press (CIP). The density of the compact at this time was 55%.
[0069] The pressed compact was sintered (step S230 in FIG. 2). For sintering, the compact was placed in a graphite die (φ=10 mm) and subjected to spark plasma sintering (SPS) at 1523 K for 10 minutes.
[0070] The sintered body of Example 3 was produced in the same manner as in Example 1, except that the magnetic field was applied in a direction perpendicular to the direction of gravity.
[0071] The sintered densities (relative densities) of the sintered bodies of Examples 1 to 3 obtained in this manner were determined by the Archimedes method in absolute ethanol. The results are shown in Table 4. The XRD patterns of the sintered bodies of Examples 1 to 3 were measured by powder X-ray diffraction. At this time, the φ angle was measured in the range of 0° to 180°, with a step width of 5°. The results are shown in Figure 9. L The value (Lotgering Factor in the 0003 direction) was calculated according to the method described above. The XRD pattern was subjected to Rietveld analysis to calculate the secondary phase. The results are shown in Table 3.
[0072] Backscattered electron images and elemental energy dispersive spectroscopy (EDS) analysis of the sintered bodies of Examples 1 to 3 were performed using a tabletop microscope. Electron backscattered diffraction (EBSD) mapping was performed using a field emission scanning electron microscope. The sintered bodies were polished successively with silicon carbide, diamond, and colloidal silica to prepare samples for EBSD. The results are shown in Figures 10 and 11. The grain size was calculated from the EBSD images. The results are shown in Table 4.
[0073] Next, the thermoelectric properties of the sintered bodies of Examples 1 to 3 were measured. The thermal diffusion coefficient (D) was measured using a laser flash analyzer Netzsch467 HyperFlash. A graphite electrode was attached to the surface of the sintered body (φ=10 mm, thickness=1 mm) to prepare a measurement sample.
[0074] The thermal conductivity κ was calculated using the following formula: κ=D×C p ×d Here, the specific heat C p is the Dulong-Petit law Cp=3×N×R / M=0.69Jg -1 K -1 where N is the formula weight per unit cell, R is the gas constant, and M is the molar mass. The density d is calculated by Archimedes' method in absolute ethanol.
[0075] The Seebeck coefficient and electrical resistivity were simultaneously measured in a He atmosphere using a thermoelectric property measurement and evaluation device (ZEM5, manufactured by Advance Riko Co., Ltd.). 3 The sintered body was processed into a rod shape and used as a sample for measurement. Electrodes were attached to the surface of the sintered body. The Hall coefficient R H The Hall coefficient was measured in AC mode using a physical property measurement system (PPMS, manufactured by Quantum Design) by sweeping the magnetic field from -5 T to +5 T. The carrier concentration n was calculated using the relation n D =1 / eR H The power factor PF and dimensionless figure of merit ZT were calculated from the obtained Seebeck coefficient, electrical resistivity, and thermal conductivity. The results are shown in Figures 12 to 17 and Table 5.
[0076] [Example 4] In Example 4, the prepared chromium silicide powder was used, and a slip-cast compact was sintered without applying a magnetic field to produce a sintered body. The sintered body of Example 4 was produced in the same manner as in Example 1, except that a magnetic field was not applied.
[0077] The sintered body of Example 4 was measured for XRD pattern, EBSD mapping, thermoelectric properties, density, grain size, f L The values of the second phase and the second phase were determined. The results are shown in FIG. 9, FIG. 11 to FIG. 17, and Tables 3 to 5.
[0078] The above will be explained in summary. For simplicity, Table 2 shows a list of the manufacturing conditions for the sintered bodies of Examples 1 to 4.
[0079] [Table 2]
[0080] FIG. 9 is a diagram showing XRD patterns of the sintered bodies of Examples 1 to 4. FIG. 10 shows an SEM image and an EDX image of the sintered body of Example 1.
[0081] According to Fig. 9, all of the diffraction peaks were indexed to CrSi2. The sintered bodies of Examples 1 and 2, to which a magnetic field perpendicular to the surface of the sintered body (pellet) shown schematically in Fig. 9 was applied, exhibited strong diffraction peaks of (0003) at 2θ = approximately 42° and (0006) at 2θ = approximately 96°, with the intensity of the (0003) diffraction peak being the strongest. This is because the c-axis of CrSi2 is the easy axis of magnetization and the diamagnetic constant |χ c | is |χ a This indicates that the sintered bodies of Examples 1 and 2 have a c-axis orientation in the thickness direction.
[0082] The XRD pattern of the sintered body of Example 2 showed the highest intensity of the (0003) diffraction peak, but also showed diffraction peaks other than (000m), unlike the sintered body of Example 1. This indicates that the degree of c-axis orientation of the sintered body of Example 2 is lower than that of the sintered body of Example 1.
[0083] On the other hand, in the XRD pattern of the sintered body of Example 3, to which a magnetic field parallel to the pellet surface was applied, the intensity of the (000m) diffraction peak was smaller than that of the (112-0) ("-" indicates an overbar for 2). This is because the sintered body of Example 3 has a c-axis orientation perpendicular to the thickness direction (parallel to the pellet surface), but the crystals are in a random state on the surface of the sintered body. In addition, the XRD pattern of the sintered body of Example 4 is similar to that of the powder in Figure 5, and it was found that the crystals in the sintered body of Example 4 are in a random state throughout.
[0084] Diffraction peaks (indicated by * in FIG. 9) indicating chromium silicide (CrSi) were confirmed in the XRD patterns of the sintered bodies of Examples 1 to 4. As shown in FIG. 10, chromium silicide was confirmed, albeit slightly.
[0085] [Table 3]
[0086] f calculated from the XRD patterns in Fig. 9 L The f values indicate that the sintered body of Example 1 has a good c-axis orientation. The sintered body of Example 2 has a c-axis orientation, but other orientations were also confirmed. L The values were negative, but this was because the c-plane was less in the measurement surface than in the random body (Example 4). In addition, all of the sintered bodies of Examples 1 to 4 contained 4 mass% of chromium silicide (CrSi) as a second phase.
[0087] FIG. 11 is a diagram showing the crystal orientations on the ND planes of the sintered bodies of Examples 1, 3, and 4, as determined by electron backscatter diffraction (EBSD).
[0088] Figure 11 also shows the ND inverse pole figure and RD inverse pole figure. Figures 11(a)-(c) show the accumulation of the (000l) plane using grayscales of different densities. Figure 11(a) shows a texture represented primarily by a dark grayscale, in which the (000l) plane accumulates on the ND plane. The inverse pole figure reveals that the a-axis and b-axis are random within the ND plane. Figure 11(b) shows a texture represented by a light grayscale, in which planes at 90 degrees to the (000l) plane accumulate. The inverse pole figure reveals that the c-axis is oriented perpendicular to the RD plane. Figure 11(c) shows a texture represented by various grayscale densities. The inverse pole figure does not reveal any accumulation of specific crystal planes, revealing that the crystals in the sintered body of Example 4 are random.
[0089] [Table 4]
[0090] According to Table 4, the sintered bodies of Examples 1 to 4 all had a relative density exceeding 96%. When the grain size was calculated from Fig. 11, it was found that the average grain size of the sintered body of Example 1 was 0.90 µm, which fell within the range of 0.88 µm to 0.92 µm.
[0091] FIG. 12 is a graph showing the temperature dependence of the electrical resistivity of the sintered bodies of Examples 1 to 4. FIG. 13 is a graph showing the temperature dependence of the Seebeck coefficient of the sintered bodies of Examples 1 to 4. FIG. 14 is a graph showing the temperature dependence of the power factors of the sintered bodies of Examples 1 to 4. As shown in FIG. FIG. 15 is a diagram showing the temperature dependence of the thermal conductivity of the sintered bodies of Examples 1 to 4. FIG. 16 is a graph showing the temperature dependence of the dimensionless figure of merit ZT of the sintered bodies of Examples 1 to 4. FIG. 17 shows the relationship between the dimensionless figure of merit ZT and f L FIG.
[0092] As described above, electrodes are provided on the surfaces of the sintered bodies of Examples 1 to 4. Therefore, it should be noted that in the sintered bodies of Examples 1 and 2, in which the c-axis is oriented in the thickness direction, the direction of the electrode plane and the c-axis are in a substantially perpendicular relationship, while in the sintered body of Example 3, in which the c-axis is oriented in the surface direction of the sintered body, the direction of the electrode plane and the c-axis are in a substantially parallel relationship.
[0093] 12, the electrical resistivity of the sintered bodies of Examples 1 to 4 all tended to increase with increasing temperature, but the electrical resistivity of the polycrystalline sintered body of Example 4 was the least temperature-dependent, and the electrical resistivity of the sintered body of Example 3 was the most temperature-dependent. It is believed that the electrical resistivity can be selectively reduced by the morphology of the sintered body, additive elements, etc.
[0094] 13, the Seebeck coefficients of the sintered bodies of Examples 1 and 2 were up to about twice as large as those of the sintered bodies of Examples 3 and 4 within the temperature range measured. In particular, the sintered body of Example 1 exhibited a large value of 160 μV / K at 500 K to 600 K. Furthermore, the Seebeck coefficients of all the sintered bodies were positive, confirming that the sintered bodies of Examples 1 to 4 were p-type semiconductors.
[0095] According to Figure 14, the power factors of the sintered bodies of Examples 1 and 2 were up to seven times larger than those of the sintered bodies of Examples 3 and 4 within the measured temperature range. This indicates that sintered bodies composed of particles primarily composed of chromium silicide (CrSi2), with the particles oriented in the c-axis direction, function as thermoelectric materials. In particular, the power factor dramatically increases in the low-temperature range of 350 K to 600 K. The thermoelectric material of the present invention can be said to be suitable for various thermoelectric cooling applications and for recovering waste heat as a power source for IoT operation, and can provide thermoelectric power generation elements for consumer use.
[0096] 15, the thermal conductivity of the sintered bodies of Examples 1 to 4 decreased with increasing temperature. The thermal conductivity of the sintered bodies of Examples 1 and 2 was slightly higher than that of the sintered bodies of Examples 3 and 4 in the measured temperature range, but no significant increase was observed.
[0097] According to Figure 16, the ZT of the sintered bodies of Examples 1 and 2 was higher than that of the sintered bodies of Examples 3 and 4 over the measured temperature range. In particular, as shown in Table 5, at 773 K, the ZT of the sintered body of Example 1 was comparable to that of a bulk single crystal. Furthermore, if the thermal conductivity or electrical resistivity of the sintered body is selectively reduced by the morphology or added elements, a further increase in ZT can be expected.
[0098] FIG. 17 shows the ZT and f of the sintered bodies of Examples 1 to 4 at 773 K. L According to Figure 17, the relationship between f L As the value approaches 1, ZT increases. However, referring to Table 5, by making the sintered body c-axis oriented, ZT becomes comparable to that of the bulk single crystal, even though the values of electrical conductivity, Seebeck coefficient, power factor, and thermal conductivity are different from those of the bulk single crystal. In particular, f L It was found that a sintered body with a high ZT value can be obtained if the value satisfies the range of 0.5 to 1. This is extremely advantageous in terms of the ease of manufacturing c-axis oriented sintered bodies compared to bulk single crystal growth, which requires advanced control and expensive equipment.
[0099] [Table 5] [Industrial Applicability]
[0100] The thermoelectric material of the present invention, although a sintered body, has thermoelectric performance equivalent to that of a bulk single crystal, and therefore can be used in thermoelectric cooling devices and power generation devices used in various electrical devices. For example, it can be used to generate electricity using waste heat from cars and trucks, as well as from nuclear power plants, thermal power plants, industrial furnaces, production lines, etc. It can also be used in radioisotope thermoelectric converters for space applications. [Explanation of symbols]
[0101] 100 Sintered body 110 particles 300 Thermoelectric power generation element 310 n-type thermoelectric material 320 p type thermoelectric material 330, 340 electrode 810 Chromium silicide powder 820 Absolute Ethanol 830 Membrane Filter 840 Porous Alumina Plate 850 Polyethylene mold 860 plastic film 870 Molded body
Claims
1. Chromium silicide (CrSi 2 ) as a main component of the sintered body, The grains are oriented in the c-axis direction, The thermoelectric material, wherein the f L value (Lotgering factor in the 0003 direction) of the sintered body in the thickness direction is in the range of 0.5 to 0.
95.
2. Said f L The thermoelectric material of claim 1 , wherein the value (Lotgering Factor in the 0003 direction) is in the range of 0.53 to 0.
95.
3. The thermoelectric material according to claim 1 , wherein the particles have a particle size in the range of 0.5 μm to 1.5 μm.
4. 4. The thermoelectric material according to claim 1, wherein the density of the sintered body is 95% or more.
5. 5. The thermoelectric material according to claim 1, wherein a portion of silicon in the chromium silicide is substituted with an element selected from the group consisting of germanium (Ge), vanadium (V), aluminum (Al), zirconium (Zr), niobium (Nb), and copper (Cu).
6. 5. The thermoelectric material according to claim 1, wherein a portion of the chromium in the chromium silicide is substituted with an element selected from the group consisting of manganese (Mn) and rhenium (Re).
7. The thermoelectric material according to any one of claims 1 to 6, wherein the particles further contain a second phase which is a chromium silicide.
8. The second phase has a cubic crystal structure and is P2 1 The thermoelectric material of claim 7 , which belongs to space group no.
3.
9. The thermoelectric material according to claim 7 or 8, wherein the second phase is contained in an amount in the range of more than 0 mass% to 6 mass%.
10. Chromium silicide (CrSi 2 A raw material powder having the above-mentioned fluorine-containing fluoride as a main component is dispersed in a solvent to prepare a raw material slurry; solidifying and molding the raw material slurry while applying a magnetic field to form a molded body; sintering the compact; The method for producing the thermoelectric material according to any one of claims 1 to 9, comprising:
11. 11. The method of claim 10, wherein the solvent is an aliphatic hydrocarbon selected from the group consisting of pentane, hexane, heptane and octane, or an alcohol selected from the group consisting of methanol, ethanol and propanol.
12. The method according to claim 10 or 11, wherein the particle size of the raw material powder is in the range of 350 nm to 550 nm.
13. The method according to any one of claims 10 to 12, wherein the magnetic field is in the range of 8T to 14T.
14. The method according to any one of claims 10 to 13, wherein forming the compact involves slip casting.
15. The method according to any one of claims 10 to 14, wherein the density of the compact is in the range of 40% or more and 70% or less.
16. The method according to any one of claims 10 to 15, wherein the sintering comprises sintering the compact at a temperature in the range of 1373K or more and 1773K or less.
17. The method according to any one of claims 10 to 16, further comprising pressing the green body prior to or simultaneously with the sintering.
18. A thermoelectric generating element including p-type thermoelectric materials and n-type thermoelectric materials alternately connected in series, A thermoelectric power generation element, wherein the p-type thermoelectric material and / or the n-type thermoelectric material is the thermoelectric material according to any one of claims 1 to 9.
Citation Information
Patent Citations
Manufacturing method of thermoelectric material
JP2001223396A
Thermoelectric conversion material, its producing method, and thermoelectric conversion module using them
JP2002009352A
Orientational thermoelectric material and manufacturing method thereof
JP2006013110A
Manufacturing method and manufacturing device of metal oxide thermoelectric material and thermoelectric conversion device
JP2007059521A
Oriented-thermoelectric material and manufacturing method thereof
JP2007115865A